The Role of Foreign Investment in Boosting Economic Growth in Southeast Asian Countries - Intanon, Ratchanok (International Journal of Economics Studies, 2024)
Foreign investment plays a significant role in accelerating economic growth in Southeast Asian countries. This article aims to explore the contribution of foreign direct investment (FDI) to regional economic growth by using secondary data from various Southeast Asian countries. The research methods employed include literature review, statistical data analysis, and a qualitative approach to identify patterns and impacts of foreign investment on the economy. The research findings show that foreign direct investment significantly contributes to economic growth by increasing capital flows, creating jobs, and facilitating technology transfer. Additionally, foreign investment also plays a role in enhancing the competitiveness of local industries and encouraging innovation. However, challenges such as overdependence on foreign investment and negative impacts on certain sectors need to be addressed to maximize its benefits. This article also discusses policies that governments can adopt to attract high-quality and sustainable foreign investment while mitigating potential risks. With a comprehensive approach, the results of this research provide deep insights into the role of foreign investment in advancing the economies of Southeast Asian countries and suggest strategies to leverage existing opportunities while addressing the challenges faced.